2020
DOI: 10.3390/f11040465
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of Propolis Extract Application in Wood Protection

Abstract: Nowadays, there is a growing interest in extending the service life of wood and wood products by applying natural substances that are harmless to humans and the environment. In this paper, propolis was used as an eco-friendly wood preservative. The aim of this study was to determine the resistance of Scots pine wood treated with the propolis extract against brown-rot fungus Coniophora puteana. The wood biodegradation was assessed by gravimetric method, as well as by the analysis of ergosterol concentration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The results show that even though its effect on wood properties was mediocre, it could be a welcome addition to wood finishes based on natural ingredients [ 149 , 157 , 158 ]. Due to the proven antifungal properties, however, propolis has also been conceived as a potential natural and an environmentally-friendly wood preservative against moulds and wood-decaying fungi [ 150 , 159 , 160 , 161 , 162 ].…”
Section: Antifungal Substances Of Animal Originmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that even though its effect on wood properties was mediocre, it could be a welcome addition to wood finishes based on natural ingredients [ 149 , 157 , 158 ]. Due to the proven antifungal properties, however, propolis has also been conceived as a potential natural and an environmentally-friendly wood preservative against moulds and wood-decaying fungi [ 150 , 159 , 160 , 161 , 162 ].…”
Section: Antifungal Substances Of Animal Originmentioning
confidence: 99%
“…Woźniak et al showed that ethanol extracts of Polish propolis of concentration exceeding 12% limited effectively decay of Scots pine wood by C. puteana [ 161 ]. The higher the propolis content in a solution was, the better antifungal effect was achieved, reaching a wood mass loss of 5.9%, 3.3%, 2.3% and 2.7% for propolis concentration of 7.5%, 12%, 18.9% and 30%, respectively.…”
Section: Antifungal Substances Of Animal Originmentioning
confidence: 99%
“…Therefore, in recent years, literature sources have reported growing interest in wood impregnation applications of natural products and synthetic compounds characterized by low impact on human health and the environment, including essential oils, chitosan, and terpenes [ 20 , 25 , 26 , 27 , 28 ]. Another example in this respect may be provided by propolis, a natural substance with various biological properties, such as antifungal, antibacterial, antioxidant, and antiviral [ 29 , 30 , 31 , 32 , 33 ]. Compared to untreated wood, the material treated with propolis extracts exhibits activity against decay fungi, such as Coniophora puteana , Trametes versicolor , and Neolentinus lepiseus [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another example in this respect may be provided by propolis, a natural substance with various biological properties, such as antifungal, antibacterial, antioxidant, and antiviral [ 29 , 30 , 31 , 32 , 33 ]. Compared to untreated wood, the material treated with propolis extracts exhibits activity against decay fungi, such as Coniophora puteana , Trametes versicolor , and Neolentinus lepiseus [ 32 , 33 ]. Literature data indicated that the extract of Polish propolis at a concentration above 12% limited the decay of pine wood caused by C. puteana [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chrysin, galangin, and pinocembrin are common flavonoids identified in propolis samples from various regions of Poland [ 4 , 8 , 9 , 19 , 20 ]. In addition, hesperetin, apigenin, kaempferol, naringenin, pinobanksin, quercetin, and phenolic acids, including caffeic, coumaric, ferulic, vanillic, gallic, and genistic acids, have also been identified in Polish propolis [ 4 , 8 , 9 , 19 , 20 , 21 ]. Fatty acids, ketones, enzymes, sterols, terpenes, minerals, and coumarins were also identified in propolis samples of various botanical origin [ 6 , 11 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%